UNIVERSITY LIFE AND AUSTRALIAN HOMES: THREE CASE STUDIES OF INTERNATIONAL MUSLIM STUDENTS IN BRISBANE - Othman, Zulkeplee (Journal of Islamic Architecture, 2014)
Despite a significant increase in enrolments of postgraduate international Muslim students within Australian universities, little is known about their perceptions of life within Australian homes while undertaking their studies. The aim of this study is to investigate the ways in which students’ cultural and religious traditions affect their use of domestic spaces within the homes in which they reside. The research found that participants faced some minor difficulties in achieving privacy, maintaining modesty and extending hospitality while able to perform their daily activities in Australian designed homes. The findings suggest that greater research attention needs to be given to the development of Australian home designs that are adaptable to the needs of a multicultural society. Australian society encompasses diverse cultural customs and requirements with respect to home design, and these are yet to be explored.